Root resorption: Focus on signs and symptoms of importance for avoiding root resorption during orthodontic treatment - Inger Kjaer (Wolters Kluwer Medknow Publications, 2014)
Introduction: This paper summarizes the different conditions, which have a well-known influence on the resorption of tooth roots, exemplified by trauma and orthodontic treatment. The concept of the paper is to summarize and explain symptoms and signs of importance for avoiding resorption during orthodontic treatment. The Hypothesis: The hypothesis in this paper is that three different tissue layers covering the root in the so-called periroot sheet can explain signs and symptoms of importance for avoiding root resorption during orthodontic treatment. These different tissue layers are; outermost - an ectodermal tissue layer (Malassez's epithelium), a middle layer - composed by the collagen-mesodermal tissue layer, and an innermost root-close innervation layer. Abnormalities in one of these tissue layers are thought to cause inflammatory processes in the periodontal membrane comparable to inflammatory processes provoked by trauma and orthodontic pressure. Inflammatory reactions are followed by resorptive processes in the periroot sheet and along the root surface. Evaluation of the Hypothesis: Different morphologies in the dentition are signs of abnormal epithelium or an abnormal mesodermal layer. It has formerly been demonstrated how demyelinization of the myelin sheaths in the peripheral nerves close to the root provoke resorption. Accordingly, conditions affecting these tissue layers can be associated not only with different morphologies but also with general symptoms and diseases (e.g., ectodermal dysplasia and hypophosphatasia).